Immigration in the United States 2016 presidential debates: a functional analysis - Yaseen, Ahmed Hasani; Mohamad Ali, Afida; Mohd Kasim, Zalina (Australian International Academic Centre, 2018)
This paper describes an analysis of the three U.S. 2016 presidential debates published in The New York Times using Benoit’s (2007a) functional theory. The three presidential debates in the U.S., which occur every four years, remain as the most sensitive political rhetoric that lead to the election of the next U.S. President. These debates include discussion of different issues between the two presidential candidates. One of these issues is immigration. The U.S. presidential debates have been researched by many on various aspects but there has not been a study that focus primarily on the issue of immigration in the three 2016 U.S. presidential debates. All statements regarding this issue between the two presidential candidates, Trump and Clinton, were extracted from these debates and analyzed using Benoit’s (2007a) functional theory. Findings revealed that attack statements occurred more than acclaims, and defences were less used than acclaims. The statements included in these debates pertained to policy (30%) and character (70%). As expected, general goals were employed more often using acclaim function rather than attack and defend. However, ideals were employed more often using defence than to acclaim and attack. Due to different contexts, situations, and participants, Benoit’s (2007a) functional theory may not be generalized for all debates. This study reveals certain inconsistencies regarding some of the hypotheses of Benoit’s (2007a) functional theory in relation to our knowledge of the presidential debates, specifically the issue of immigration.